1997
DOI: 10.1152/ajprenal.1997.272.5.f561
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and homeostatic roles of nitric oxide in the normal kidney

Abstract: Nitric oxide (NO) is an important molecular mediator of numerous physiological processes in virtually every organ. In the kidney, NO plays prominent roles in the homeostatic regulation of glomerular, vascular, and tubular function. Differential expression and regulation of the NO synthase (NOS) gene family contribute to this diversity of action. This review explores recent advances in the molecular and cell biology of the NOS isoforms and relates these findings to functions of NO in the control of normal renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
259
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(275 citation statements)
references
References 142 publications
10
259
1
5
Order By: Relevance
“…In that respect, rats that received NTG displayed attenuated renal vasoconstrictive response to pneumoperitoneum, whereas rats pretreated with L-NAME displayed a higher sensitivity to this surgical procedure, suggesting a greater dependence of the kidney on NO as a beneficial counterregulatory system during pneumoperitoneum. This conclusion is compatible with the notion that NO plays a prominent role in the control of renal hemodynamics and tubular function (28,29). NO is constitutively produced from its precursor, L-arginine, by the enzyme endothelial NO synthase and acts on adjacent smooth muscle cells to exert vasodilatory tone on the renal microvasculature, primarily the afferent arteriole.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In that respect, rats that received NTG displayed attenuated renal vasoconstrictive response to pneumoperitoneum, whereas rats pretreated with L-NAME displayed a higher sensitivity to this surgical procedure, suggesting a greater dependence of the kidney on NO as a beneficial counterregulatory system during pneumoperitoneum. This conclusion is compatible with the notion that NO plays a prominent role in the control of renal hemodynamics and tubular function (28,29). NO is constitutively produced from its precursor, L-arginine, by the enzyme endothelial NO synthase and acts on adjacent smooth muscle cells to exert vasodilatory tone on the renal microvasculature, primarily the afferent arteriole.…”
Section: Discussionsupporting
confidence: 88%
“…These results are at odds with those reported that administration of Ro 61-0612, a mixed ET A and ET B blocker, attenuated the fall in GFR and oliguria during pneumoperitoneum (1,39). It should be emphasized that these authors applied similar IAP and drug infusion protocol; however, the pneumoperitoneum was established for Because endothelium-derived NO is important in the regulation of RBF and kidney function (28,29), we tested the hypothesis of whether altered activity of the NO system may be involved in the pathogenesis of the reduced RBF and kidney function characterizing pneumoperitoneum. Indeed, the most prominent finding in the present study was the effects of NO modulations on the adverse renal effects of elevated IAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…iNOS (NOS-2) is an isoform of nitric oxide synthase found in renal tubules, vascular smooth muscle, fibroblasts, and macrophages (13). Its gene expression is increased after ischemic ARF, and persistent high concentrations of NO result.…”
mentioning
confidence: 99%
“…NOS2 is expressed in the endothelium of glomerular capillaries and afferent and efferent arterioles, renal arteries, and descending vasa recta, as well as in proximal tubule and medullary thick ascending limb. NOS3 is also expressed in tubules, including S3 segments of the proximal tubule, medullary thick ascending limb, and collecting duct, in addition to arcuate arteries and vasa recta bundles (Kone, BC, 1997). Both in vivo and in vitro studies have provided conflicting results regarding NOS expression and NO production in diabetes.…”
Section: Nitric Oxidementioning
confidence: 99%